2007
DOI: 10.1128/jvi.01990-06
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Decrease in Viremia in Macaques Chronically Infected with Simian Immunodeficiency Virus SIVmac251 after Therapeutic DNA Immunization

Abstract: Rhesus macaques chronically infected with highly pathogenic simian immunodeficiency virus (SIV) SIVmac251 were treated with antiretroviral drugs and vaccinated with combinations of DNA vectors expressing SIV antigens. Vaccination during therapy increased cellular immune responses. After the animals were released from therapy, the virus levels of 12 immunized animals were significantly lower (P ‫؍‬ 0.001) compared to those of 11 animals treated with only antiretroviral drugs. Vaccinated animals showed a persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 37 publications
8
55
2
Order By: Relevance
“…During the chronic phase, immune control is important, and small changes in the number of effector cells can have a large effect in the model. Increasing the number of CD8 ϩ T cells by therapeutic vaccination (58,94) or depleting them with a monoclonal antibody (46,67,85) during the chronic phase of the infection indeed markedly affects the viral load. The former is surprising because one would expect a minor effect of therapeutic vaccination, since there is enough antigen available to stimulate the CD8 ϩ T cells.…”
Section: Prophylactic Vaccinationmentioning
confidence: 99%
“…During the chronic phase, immune control is important, and small changes in the number of effector cells can have a large effect in the model. Increasing the number of CD8 ϩ T cells by therapeutic vaccination (58,94) or depleting them with a monoclonal antibody (46,67,85) during the chronic phase of the infection indeed markedly affects the viral load. The former is surprising because one would expect a minor effect of therapeutic vaccination, since there is enough antigen available to stimulate the CD8 ϩ T cells.…”
Section: Prophylactic Vaccinationmentioning
confidence: 99%
“…The vaccination of HIV-1-infected individuals (67) or SIV-infected macaques (47,49,56,68) with these vaccine modalities results in an expansion of virus-specific adaptive CD4 ϩ and CD8 ϩ T cells that is nevertheless insufficient to control viral replication in the long term. In SIV mac251 -infected macaques we have previously demonstrated a correlation between vaccine-induced CD4 ϩ and CD8 ϩ T cell responses and set point viremia following ART suspension (49), and the phenotypic characterization of SIV-specific CD8 ϩ T cells demonstrated an inverse correlation with Ag-specific central memory CD8 ϩ T cells and plasma virus level (68).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of therapeutic vaccines to expand memory CD4 ϩ T cell responses has been correlated with the transient control of viral replication (56). Thus, approaches able to further expand SIV-specific memory responses may synergize with vaccination.…”
Section: Il-15 Abrogates the Ability Of Vaccination To Decrease Plasmmentioning
confidence: 99%
“…Tcm are decimated may favor recovery of these cells and promote immunologic control of virus load following discontinuation of ART. Therapeutic vaccination given during 20 to 24 wk of ART in SIVmac251-infected macaques was successful in inducing virus control following termination of ART, although the effect of vaccination on CD4 1 Tcm was not reported [22,25].Ad-mediated expression of IL-15 in addition to viral genes may have had a detrimental effect on immune control of virus infection in our study, as animals in the Ad-SIV/IL-15 group tended to have lower IFN-g ELISPOT responses following vaccination along with higher virus loads following termination of ART relative to the Ad-SIV group. While not specifically addressed here, other studies have shown that IL-15 immunotherapy during SIV infection increases proliferation and activation of CD4…”
mentioning
confidence: 99%
“…While emphasis has been placed on evaluating immunity to prophylactic vaccines, no studies to our knowledge have addressed the nature of the immune response to Ad-based vaccination in established HIV infection. This is an important consideration given the interest in therapeutic vaccination as a means of controlling HIV [21][22][23][24][25]. In addition to enhancing the magnitude and polyfunctional nature of Ag-specific CD4 [30,31].…”
mentioning
confidence: 99%